Anesthesia management using remimazolam for coronary artery bypass grafting and aortic valve replacement in a patient with severe cardiac dysfunction: A case report - Tomoki Sagawa; Yusuke Ishida; Tomomi Sasaki; Maiko Hosokawa; Kiyoko Bito; Katsunori Oe (SAGE Open Medical Case Reports)
Remimazolam, a short-acting benzodiazepine approved for use in general anesthesia in Japan in 2020, has cardiovascular stability superior to conventional anesthetics. Anesthesia management using remimazolam of a patient with impaired cardiac function and several complications is reported. A man in his 50s with hypertension, diabetes mellitus, and chronic kidney disease (G 5) on dialysis came to our hospital with a chief complaint of exertional dyspnea and chest tightness, and a close examination showed stenoses of three coronary arteries. The patient was managed under anesthesia using remimazolam as a sedative because anesthetics could easily induce circulatory failure. Cardiopulmonary bypass was initiated without causing any circulatory failure, and coronary artery bypass grafting and aortic valve replacement were performed. The patient was successfully weaned with a small dose of catecholamine. Remimazolam was selected for this patient because of its minimal effect on cardiac rhythm, and the anesthesia was safely administered.